Hypothyroidism: The difficulty in attributing symptoms to their underlying cause - Jansen, Heleen I.; Boelen, Anita; Heijboer, Annemieke C.; Bruinstroop, Eveline; Fliers, Eric (Frontiers in Endocrinology, 2023)
Common symptoms of overt hypothyroidism are non-specific and include fatigue, lethargy, and dry skin. Although the diagnosis is considered to be straightforward, no single symptom can be used to identify patients with overt hypothyroidism, while many patients with subclinical hypothyroidism are asymptomatic. A large population-based study on the spectrum of symptoms in subclinical hypothyroidism showed similar rates of thyroid disease-related symptoms compared with euthyroid subjects, while the TSH concentration had no impact on symptom score. Together, these findings make it challenging to attribute symptoms to their underlying cause. This is also true in the case of unexplained persistent symptoms in levothyroxine-treated patients. Although generally considered a life-long replacement therapy, successful thyroid hormone discontinuation resulting in euthyroidism has been reported in approximately one third of patients. Thus, we overtreat patients with (subclinical) hypothyroidism, highlighting the importance of reliable diagnostic criteria. The diagnostic process, including the implementation of robust TSH and FT4 reference intervals, is especially challenging in specific situations including aging, pregnancy, non-thyroidal illness, and central hypothyroidism. There is a clear need for improved adherence to current guidelines from scientific societies and for willingness to manage symptoms without a clear pathological correlate, especially in the case of mild TSH elevations. This review will highlight recent literature on this topic and offers some practice points.